HUMOR ENGLISH TEACHING MATERIAL FOR IMPROVING STUDENTSÃ¢â¬â¢ SPEAKING SKILL WITH HIGH AND LOW LEARNING MOTIVATION - Syafiq, Ahmad Nur; Saleh, Mursid (Language Circle: Journal of Language and Literature, 2012)
This study aimed at investigating the effectiveness of humor as English foreign language teaching material to improve studentsÃ¢â¬â¢ speaking skill with of high or low motivation for the students and the effect that the use of humor gives to their teaching. This study was quasi experimental research named two-way (two-by-two) factorial design. The subjects were 80 students of STAIN Kudus, 40 students in the experimental group and 40 students in the control group. Both groups were distributed the pre-test to measure students speaking skill. For treatment, Shades (1996) classification of verbal humor was used. The results revealed that humor as teaching material has significant effect on the studentsÃ¢â¬â¢ speaking skill to those who have high and low learning motivation. The students expressed that humor in the classroom situation affected their learning positively to those who have high or low motivation rather than conventional material.